Conversation Analysis and Its Implications to Language Teaching - Hidayat, Didin Nuruddin (TARBIYA: Journal of Education in Muslim Society, 2019)
AbstractThe present study analyzed the use of Conversation Analysis in casual conversation and how it can serve as a potential means in language teaching. Casual conversation concerns the type of conversation that people do when they talk just for the sake of talking (Eggins & Slade, 1997). This includes daily conversations among people. Employing a qualitative research methodology, data were taken from a casual conversation taking place in Australia regarding a birthday party preparation between a husband and a wife whose native language is Bahasa Indonesia. Data were first transcribed in Bahasa Indonesia using CA conventions, and then were translated into English. The transcription of the conversation attempted to follow the guidelines proposed by Cook (1990) and Bailey (2008). The study found that turn-taking systems, adjacency pairs, overlaps, response tokens, and repairs were evident from the analysis of conversation. The conversation confirms the theories of CA: the occurrence of a large number of response tokens, such as mm hm or yes, various types of adjacency pairs, each speaker speaks one at a time even though there are several gaps and overlaps, and so forth. The study drew the implication of CA to language teaching. CA contributes to language teaching in terms of offering not only the authentic real-life communication, but also the authentic spoken interaction which will encourage learners to be able to produce authentic utterances. Also, CA can serve as a potential means to shape the students’ ability as active participants in the learning process.AbstrakStudi ini menganalisis penggunaan Analisis Percakapan (Conversation Analysis, selanjutnya CA) dalam percakapan kasual dan mengulas bagaimana CA dapat berfungsi sebagai sarana yang potensial untuk dipergunakan dalam pengajaran bahasa. Percakapan kasual diartikan sebagai jenis percakapan yang dilakukan orang ketika mereka berbicara dengan topik sehari-hari (Eggins & Slade, 1997). Penelitian ini menggunakan metodologi penelitian kualitatif dengan mengambil data dari percakapan kasual antara suami istri yang berlangsung di Australia mengenai persiapan pesta ulang tahun. Bahasa ibu para pembicara adalah Bahasa Indonesia. Data pertama-tama ditranskripsikan dalam Bahasa Indonesia menggunakan konvensi CA, dan kemudian diterjemahkan ke dalam bahasa Inggris. Transkripsi percakapan mengikuti panduan Cook (1990) dan Bailey (2008). Studi ini menemukan bahwa sistem turn-taking, adjacency pairs, overlaps, token response, dan repair terbukti dari analisis percakapan. Hasil penelitian mengkonfirmasi teori-teori CA: terjadinya sejumlah besar token response, seperti mm hm atau ya, berbagai jenis adjacency pairs, masing-masing pembicara berbicara satu per satu walaupun ada beberapa celah dan overlaps, dan sebagainya. Studi ini juga menggali implikasi CA terhadap pengajaran bahasa. CA berkontribusi pada pengajaran bahasa dalam hal menawarkan tidak hanya komunikasi kehidupan nyata yang otentik, tetapi juga interaksi lisan yang otentik yang akan mendorong peserta didik untuk dapat menghasilkan ucapan-ucapan otentik. Selain itu, CA dapat berfungsi sebagai sarana potensial membentuk kemampuan siswa untuk berperan aktif dalam proses pembelajaran.How to Cite: Hidayat, D. N. (2019).   Conversation Analysis and Its Implications to Language Teaching  . TARBIYA: Journal of Education in Muslim Society, 6(2), 197-209. doi:10.15408/tjems.v6i2. 15138.